Evaluation of bone morphology in posterior mandible - a cone-beam computed tomography (CBCT) based study - Arif, Aysha; Khan, Farhan Raza (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the position of the root apices of posterior teeth of mandible with inferior alveolar nerve canal and the cortical bone on cone beam computed tomography. Method: The retrospective study was conducted from September to October 2021 at the Aga Khan University Hospital, and comprised cone beam computed tomography scans between November 2017 and October 2021 scans of healthy individuals of either gender aged 18-71 years with healthy, untreated, mandibular posterior teeth bilaterally. Shortest distance from apices of the mandibular posterior teeth to the border of inferior alveolar nerve canal, and to the mandibular buccal cortex were measured on the scans. Data was analysed using SPSS 23. Result: Of the 106 scans, 55(52%) were males and 51(48%) were females. Of the 746 33teeth in the scans, 385(51.6%) were present in the scans of males and 361(48.4%) in those of the females. For all mandibular posterior teeth, the distances in females were shorter than males, but for the distance from root apices to the IAN canal, the difference between genders was significant for the roots of second premolar and second molar only on the left side (p0.05). Regarding the distance from the root apices to the buccal cortex, no significant difference was found between the genders, for each type of tooth, (p>0.05). Correlations between the distance from apex to inferior alveolar nerve (r<0.30) and between age and apex to buccal cortex distance (r<0.28) were weak. Conclusions: Procedures planned apical to second premolar and second molar teeth can potentially damage the inferior alveolar nerve. Key Words: Inferior alveolar canal, Cone bone computed tomography, Root apices.